2020
DOI: 10.5194/nhess-2020-185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Drought on Soil Moisture Trends across Brazilian Biomes

Abstract: Abstract. Over the past decade, Brazil has experienced severe droughts across its territory, with important implications for soil moisture dynamics. Soil moisture variability has a direct impact on agriculture, water security, and ecosystem services. Nevertheless, there is currently little information on how soil moisture across different biomes respond to drought. In this study, we used satellite soil moisture data from the European Space Agency, from 2009 to 2015, to analyze differences in soil moist… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Temporal variability in soil moisture is an important indicator of alterations in the water cycle (Rossato et al, 2017), a crucial indicator of the potential impacts of climate change on water and land assets. Ribeiro et al (2021) analysed the impact of droughts (2009)(2010)(2011)(2012)(2013)(2014)(2015) in soil moisture and suggested that the Pantanal is able to accumulate soil moisture during drought events, because they found an increasing trend in this variable even in 2012, when the biome presented a reduction of 81% of its total flooded area. This fact might indicate a water stress threshold at which the region is capable of maintaining water availability through the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal variability in soil moisture is an important indicator of alterations in the water cycle (Rossato et al, 2017), a crucial indicator of the potential impacts of climate change on water and land assets. Ribeiro et al (2021) analysed the impact of droughts (2009)(2010)(2011)(2012)(2013)(2014)(2015) in soil moisture and suggested that the Pantanal is able to accumulate soil moisture during drought events, because they found an increasing trend in this variable even in 2012, when the biome presented a reduction of 81% of its total flooded area. This fact might indicate a water stress threshold at which the region is capable of maintaining water availability through the soil.…”
Section: Discussionmentioning
confidence: 99%
“…According to Junqueira et al [28], recent droughts have generated a reduction in the aquifer recharge and in the reservoir level in the Tocantins River basin, Brazilian savanna, negatively affecting the hydropower production. In addition, Ribeiro et al [74] report a reduction in soil moisture and primary productivity in the Brazilian savanna in recent years. On the other hand, the second third of the period (1973-1995) showed a high incidence of wet months (47.9% of the total) and a low incidence of drought months (20.1%).…”
Section: Hydrological Retrospective (Hr) and Historical Droughtsmentioning
confidence: 99%
“…O bioma Mata Atlântica corresponde a cerca de 13% do território brasileira (1.110.182 km²), ocupando todo o território costa continental do Brasil (Ribeiro et al, 2020). Entre os biomas brasileiros, a Mata Atlântica é o mais degradado, tendo apenas 12% do o bioma original preservado (SECOM, 2012).…”
Section: Mata Atlânticaunclassified